2013
DOI: 10.1049/iet-com.2012.0499
|View full text |Cite
|
Sign up to set email alerts
|

Robust spectrum sensing based on statistical tests

Abstract: Spectrum sensing, in particular, detecting the presence of licensed or incumbent users in licensed spectrum, is one of the pivotal tasks in cognitive radio network. In this paper, we tackle the spectrum sensing problem by using statistical test theory and derive novel spectrum sensing approaches. We apply the classical Kolmogorov-Smirnov (KS) test under the assumption that the noise probability distribution is known. However, as in practice, the exact noise distribution is unknown, a sensing method for Gaussia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Considering the small number of samples and the special sensing scenario about detecting a wideband signal in a zero mean Gaussian noise, it is shown that the optimal test in signal detection is Student's t test [31]. In order to construct the test statistic in accordance with Student's t distribution, we denote, respectively, X k and S 2 k as the mean and variance of the samples in the kth subband,…”
Section: Statistical Model Of the Received Small Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the small number of samples and the special sensing scenario about detecting a wideband signal in a zero mean Gaussian noise, it is shown that the optimal test in signal detection is Student's t test [31]. In order to construct the test statistic in accordance with Student's t distribution, we denote, respectively, X k and S 2 k as the mean and variance of the samples in the kth subband,…”
Section: Statistical Model Of the Received Small Samplesmentioning
confidence: 99%
“…In order to improve the reliability, Dempster-Shafer (D-S) theory of evidence [22][23][24][25][26][27][28][29][30] is used to make a final decision. As in [31], in the proposed method, Student's t distribution of a reduced number of samples is used. The main contribution stands in the proposition of two new BPA functions to evaluate the credibility of the collected small samples from a wideband signal and the combination of BPA functions in order to make a more reliable decision.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that this combiner does not demand the CSI, and it provides superior performance compared to MRC. The Goodness of fit test based sensing (GoFT) using Anderson Darling (AD) and Jarque Bera (JB) tests check for the distribution of test statistic under null hypothesis and is independent of the noise distribution [9][10][11]. These statistical methods were primarily meant to measure the strength of evidence for drawing an accurate decision in hypothesis testing based on a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In a two-sample K-S test, the basic procedure involves computing the empirical cumulative distribution function of given datasets, and comparing with each other. It has been applied to fast spectrum sensing [22,23] and feature selection in emotional speech recognition [24].…”
Section: Introductionmentioning
confidence: 99%